Factors associated with dietary patterns (DPS) and nutritional status among pregnant women in AM-HDSS, South Ethiopia - Fikadu, Teshale; Tamiru, Dessalegn; Ademe, Beyene Wondafrash (Frontiers in Nutrition, 2024)
Background: Malnutrition during pregnancy increases the risk of chronic illness later in life and adverse birth outcomes in subsequent generations. Hence, the aim of this study was to assess factors associated with dietary patterns and nutritional status of pregnant women in South Ethiopia. A community-based cross-sectional study was conducted using a validated, a pre-tested, interviewer-administered structured questionnaire. Principal component factor analysis was employed to determine dietary patterns. Bivariable and multivariable ordinal logistic regression analyses were used to identify associated factors. The dietary habits of pregnant women were best explained by three distinct dietary patterns. Urban dwellers (AOR= 2.18; 95% CI: 1.33, 3.59), high socio-economic status (AOR= 2.43; 95% CI: 1.68, 3.51), middle socio-economic status (AOR= 1.72; 95% CI: 1.19, 2.48), primigravida (AOR= 1.72; 95% CI: 1.07, 2.78), and multigravida (AOR= 2.08; 95% CI: 1.39, 3.10) were high likelihood to consume the highest tercile of "Cereals-Pulses and Dairy". Attending formal education (AOR= 1.60; 95% CI: 1.02, 2.51), from higher socioeconomic status (AOR= 1.56; 95% CI: 1.02, 2.38), experiencing food aversion (AOR= 1.98; 95% CI: 1.16, 3.39), and had good dietary knowledge (AOR= 2.16; 95% CI: 1.08, 4.32) were associated with a higher tercile consumption of "Nutrient-Dense" food compared to those without formal education, no food aversion and had poor dietary knowledge, respectively. Not attending formal education (AOR= 2.22; 95% CI: 1.48, 3.36), had decision-making autonomy (AOR= 1.91; 95% CI: 1.26, 2.90), and had good dietary knowledge (AOR= 1.86; 95% CI: 1.13, 3.08) were found to consume the highest tercile of "Leafy local food" compared to their counterpart. Consumption of lower terciles "Nutrient-Dense" food (AOR=1.63; 95% CI: 1.07, 2.47) and "Leafy local food" (AOR= 2.32; 95% CI: 1.54, 3.51) were found to be factors associated with under nutrition during pregnancy. Three distinct dietary patterns were identified. Factors associated with these major dietary patterns included place of residence, socio-economic status, educational level, dietary knowledge, food aversion, number of pregnancies, and maternal decision-making autonomy. Under nutrition among pregnant women was found to be high and associated with the consumption of 'Nutrient-Dense' and 'Leafy local' foods.